2018
DOI: 10.3390/su10124839
|View full text |Cite
|
Sign up to set email alerts
|

Internal Differentiation within the Rural Migrant Population from the Sustainable Urban Development Perspective: Evidence from China

Abstract: Population mobility and attendant issues, especially housing issues, have a major impact on sustainable urban development. In the urbanization process, a number of micro-communities with various social characteristics have come to compose the rural migrant population (RMP), resulting in internal differentiation. This study aims to reveal the demographic structure of this specific group, and to analyze the effects of the mechanism between population flow trends and sustainable urban development, taking housing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Therefore, a new category of migrant workers has appeared: skilled migrant workers. Scholars have recognized the heterogeneity of the migrant population [11][12][13]. In this paper, we divide migrants into two groups: skilled migrants and labor migrants.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, a new category of migrant workers has appeared: skilled migrant workers. Scholars have recognized the heterogeneity of the migrant population [11][12][13]. In this paper, we divide migrants into two groups: skilled migrants and labor migrants.…”
Section: Introductionmentioning
confidence: 99%
“…According to the 6th population census in 2010, skilled migrants comprised 14.4% of total migrants [14], and this proportion rose to 25.7% according to the 1% population sampling survey in 2015. Studies have reported that skilled migrants' occupations, earnings, consumption habits, and lifestyles are significantly different from their less-educated counterparts because they received a higher education [11][12][13]. Although skilled migrants are also mainly employed in the manufacturing, transportation, low-end service, and wholesale and retail trade industries, similar to labor migrants, skilled migrants mostly work in management, professional, or technical positions, which are higher positions than those occupied by labor migrants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the early stage of development, there is a special binary opposition between urban and rural areas. Cities absorb a large amount of rural labor through the industrialization process and the gap between urban and rural areas gradually becomes prominent [1][2][3]. With the process of industrialization, cities further spread their development effects to the countryside and drive rural development, gradually forming the "core-periphery" [4], "growth pole" [5] and "circle layer" models [6].…”
Section: Introductionmentioning
confidence: 99%
“…Davoodi and Moradi (2018) used a mixed data clustering algorithm based on fuzzy k-prototypes algorithm to determine the number of rules in each layer from a deep learning framework, called deep rule-based fuzzy system (DRBFS), with the objective of predicting mortality at an emergency unit. Deng et al (2018) proposed a new method based on the k-medoids algorithm to analyze the rural migrant population in China. The authors used PAM algorithm with the Gower distance.…”
Section: Partitionalmentioning
confidence: 99%